Structure integrity evaluation of gas protective wall for new construction method using strength test and numerical analysis - Song, Doo Guen; Jung, Seung Ho; Kim, Eui Soo (Journal of Mechanical Science and Technology, 2021)
Gas protective walls are safety elements that can withstand the pressure of fires or explosions caused by gas leaks, thus preventing the spread of explosion damage to other facilities or operators. However, in the new construction or expansion of gas facility rooms in existing buildings, the barrier must often be built even if it does not satisfy the legal standards regarding the accepted construction methods. In these cases, the gas barrier for the existing building should be constructed by the new construction method using chemical anchor bolts. However, no performance evaluation data or reliable engineering verification results are available for the entire gas facility room based on actual experiments. In this study, based on a review of regulations on gas barriers, the protective performances of the new barriers were compared in terms of displacement, rotation angle, rebar strain, and yield value of the concrete surface through actual strength demonstration experiments. Based on these results, the protection performance of an entire gas facility room that could not be constructed and tested in real time was evaluated by a fluid structure interaction (FSI) analysis using the TNT(Trinitrotoluene) equivalency method and three-dimensional AUTODYN.
Keywords: Actual experiments; Concrete surface; Construction method; New constructions; Protection performance; Protective performance; Structure integrity; Verification results; 3D AUTODYN; Chemical anchor bolt; Gas protective wall; Structural integrity; TNT equivalent method